The Necessity of Implementing a Quality Management System in the Romanian Medical Units. An Approach from the Patients Point of View - Roxana Sarbu; Adriana Zanfir (Amfiteatru Economic Journal, 2011)
The medical services organizations activate in a specific featured environment, extremely sensitive, dynamic and most of the times unpredictable. In order to develop their activity at a high qualitative level, medical units must possess the ability of accepting the changes that might occur, of identifying and valorizing the possible opportunities and, at the same time, they must have the ability of avoiding risks as much as possible. The medical field considers quality a variable which is hard to quantify and which could be perceived as the result of the comparison between the medical service desired/requested by the client and the provided health service or the extent to which the provided service corresponds to the client's expectations. The current paper refers to the growing problems of the Romanian health system and it also takes into consideration the deficiencies which influence the quality of the provided services. The approach manner of this particular theme is realized by taking into account the quality management system. At the same time, there is made an analysis of the consumer's perception regarding both the quality of health services and the necessity of implementing a quality management system in all units providing health services. The research is based on a rich study of the professional literature, on articles and scientific papers in this field of activity. The data was collected by applying a questionnaire to the population which has been provided medical services over the past year.
Keywords: I10; I18; I19; 330; quality management system; medical units; health services; quality; quality standards